1962
DOI: 10.1111/j.1469-1809.1962.tb01518.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the genetics of galactosaemia

Abstract: SummaryGalactose‐1‐phosphate uridyltransferase has been determined, by a manometric method, in the lysed erythrocytes of galactosaemic children and their families and in normal controls. Parents of galactosaemic children have about 64 % of the enzyme activity found in controls, while homozygous individuals have little or none. There is a slight overlap of enzyme levels in the control and heterozygote groups. This renders a definite placing of borderline cases impossible.There is some evidence to suggest that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

1964
1964
1993
1993

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 8 publications
2
8
1
Order By: Relevance
“…"Classic galactosemia," that is, infants with appropriate clinical signs at the time physicians were notified of abnormal screening results (by telephone on the day of the test, if strikingly abnormal), was certain in two of the 141,402 infants, giving an incidence of one in 70,000. This frequency was remarkably similar to an early estimate of the incidence of galactosemia at birth in Great Britain (15), projected from clinical reports of the disease.…”
Section: Discussionsupporting
confidence: 85%
“…"Classic galactosemia," that is, infants with appropriate clinical signs at the time physicians were notified of abnormal screening results (by telephone on the day of the test, if strikingly abnormal), was certain in two of the 141,402 infants, giving an incidence of one in 70,000. This frequency was remarkably similar to an early estimate of the incidence of galactosemia at birth in Great Britain (15), projected from clinical reports of the disease.…”
Section: Discussionsupporting
confidence: 85%
“…There was one death in this group, that of the patient referred to earlier who died from E coli septicaemia at 4 days. Three siblings of the study patients died of liver disease around 6 weeks of age and were presumed affected. Two came from areas that were being screened at the time of their birth, but it could not be confirmed that neonatal screening had been performed in these cases.…”
Section: Resultsmentioning
confidence: 99%
“…The metabolic lesion in this disorder is the absence of transferase activity (Isselbacher et aL, 1956). Heterozygotes for galactosemia have approximately one-half the activity of transferase in blood cells as normal individuals and there is very little overlap between the heterozygous range and the normal range (Kirkman and Bynum, 1959;DonneU et al, 1960;Hsia et al, 1960;Schwarz et al, 1961 ;Weinberg, 1961). Therefore, it is possible to determine the frequency of heterozygous individuals in the general population by measuring transferase in blood cells (Hansen et al, 1964;Beutler et al, 1966;Brandt, 1967;McGuiness and Saunders, 1967).…”
Section: U D P G a L " Udpglumentioning
confidence: 92%